2015
DOI: 10.1136/vr.102522
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular administration of alfaxalone for sedation in rabbits

Abstract: Alfaxalone is a neuroactive steroid derivative of pregnanedione that was recently reintroduced to the market for use as an induction agent in small animal anaesthesia. The aim of this study was to determine an intramuscular alfaxalone dose for safe immobilisation. Ten healthy New Zealand white rabbits were used to evaluate a single intramuscular injection of alfaxalone. The design of the study was a three-way, complete block, cross-over trial to compare the effect of alfaxalone at three doses (4, 6 and 8 mg). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 24 publications
1
31
2
Order By: Relevance
“…This study builds on initial investigations of alfaxalone administered intramuscularly in rabbits. 13,16 The current study demonstrated that alfaxalone in combination with other sedatives produces prolonged and reliable sedation and, in some combinations, can provide anesthesia. Compared with the use of alfaxalone alone, the addition of midazolam increased the duration of sedation by an average of 25 min, and the addition of dexmedetomidine increased the duration of sedation by an average of 117 min.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This study builds on initial investigations of alfaxalone administered intramuscularly in rabbits. 13,16 The current study demonstrated that alfaxalone in combination with other sedatives produces prolonged and reliable sedation and, in some combinations, can provide anesthesia. Compared with the use of alfaxalone alone, the addition of midazolam increased the duration of sedation by an average of 25 min, and the addition of dexmedetomidine increased the duration of sedation by an average of 117 min.…”
Section: Discussionmentioning
confidence: 56%
“…The average duration of sedation in our study was 40 min for the 6-mg/kg alfaxalone group, which is lower than the 51.8 min reported elsewhere for the same dosage. 13 That study used male rabbits that were similar in age to our animals, so the difference may be due to sex-associated differences in sedation duration with intramuscular alfaxalone in rabbits. In addition, the relatively low numbers of animals in each study group may help to explain this observed difference.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoventilation is a common occurrence at induction and during general anesthesia in rabbits (24, 12). A frequent alternative to orotracheal intubation is the use of a facemask.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the dose of IM alfaxalone would also increase the risk for cardiorespiratory side effects, as has been demonstrated in dogs, cats and rabbits (Huynh et al 2015;Tamura et al 2015a;Tamura et al 2015b). Moreover, because alfaxalone is only available in Europe at a concentration of 10 mg mL -1 doses higher than 5 mg kg -1 would result in unacceptably high IM injection volumes for small rodents.…”
Section: Accepted Manuscriptmentioning
confidence: 99%